PERAN MODEL KETELADANAN PENGASUH PONDOK PESANTREN AL IHSAN TERHADAP AKHLAK SANTRI - Wahid, Abdul Rohman; Benny Prasetiya (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The formation of a strong and dignified character is the main challenge in individual development. One effective approach is through example, where positive role models become the main foundation in guiding individuals to acquire and internalize values, morality and integrity in their lives. This research highlights exemplary education at the Al-Ihsan Islamic Boarding School, with a focus on the exemplary forms shown by caregivers. The research method used is qualitative with data sources obtained through observation, field notes, interviews and personal documents. The results of the research concluded that the example of kiyai at the Al-Ihsan Islamic Boarding School includes several aspects, including patience, devotion to worship, humility, asceticism, good morals, self-confidence in preaching, and exemplary politics. It is hoped that an in-depth understanding of these forms of example can make a positive contribution to the formation of the character of students, not only in the realm of religion, but also in daily life and participation in society.